Business management in the era of rasulullah s.a.w from the prespectives of al-Quran and hadith / Zanirah Mustafa@Busu - Mustafa @ Busu, Zanirah (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2016)
Business or trade (tijarah) is a profession which is encouraged and recognized by Islam as an important profession in the human life. Business and trade is not only seen as an important element for individuals, it also plays an important role in community and the nation. Rasulullah SAW and his companions were the famous traders during the highlighted era of Islam. Rasulullah SAW had shown good examples in the business and trade profession. All business transactions need to be done in accordance to the principals of Islamic business management in order to abide the rules of Allah. Therefore, Islam has created the guidelines for the activities of muamalat which is in accordance with the fitrah. The main goal in the life of a Muslim is to seek the blessings of Allah and become a servant that pleases Allah SWT. Islam also stresses that effort is an important key in performing any types of deeds